Potency of Microalgae as Biodiesel Source in Indonesia - Hadiyanto Hadiyanto; Widayat Widayat; Andri Cahyo Kumoro (International Journal of Renewable Energy Development, 2012)
Within 20 years, Indonesia should find another energy alternative to substitutecurrent fossil oil. Current use of renewable energy is only 5% and need to be improved up to 17%of our energy mix program. Even though, most of the area in Indonesia is covered by sea, howeverthe utilization of microalgae as biofuel production is still limited. The biodiesel from currentsources (Jatropha, palm oil, and sorghum) is still not able to cover all the needs if the fossil oilcannot be explored anymore. In this paper, the potency of microalgae in Indonesia was analysed asthe new potential of energy (biodiesel) sources.